2018
DOI: 10.4103/sni.sni_22_18
|View full text |Cite
|
Sign up to set email alerts
|

Multiple meningiomas in two male-to-female transsexual patients with hormone replacement therapy: A report of two cases and a brief literature review

Abstract: Background:Exogenous sex hormones may play a role in meningioma development and growth. Thus, transsexual patients being on long-standing hormone replacement therapy (HRT) may be at particular risk for meningioma development and growth. Here we present two cases of two male-to-female transsexual patients taking HRT for an extended period of time with both patients requiring surgical treatment at our institution due to multiple growing meningiomas.Case Description:The first patient was a 50-year-old genetic mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…The majority (n = 10) were managed upfront with surgical intervention, and most also had CPA stopped at the same time (n = 8), except for one who had the dose tapered. 19 Two transgender persons were managed by cessation of CPA only without surgical intervention. 21,22 Synthesis of individual meningioma associated with included case reports Table 4 summarizes the individual meningioma (n = 35) described within the case reports included within this systematic review.…”
Section: Results Of Individual Case Reports and Associated Meningiomamentioning
confidence: 99%
See 2 more Smart Citations
“…The majority (n = 10) were managed upfront with surgical intervention, and most also had CPA stopped at the same time (n = 8), except for one who had the dose tapered. 19 Two transgender persons were managed by cessation of CPA only without surgical intervention. 21,22 Synthesis of individual meningioma associated with included case reports Table 4 summarizes the individual meningioma (n = 35) described within the case reports included within this systematic review.…”
Section: Results Of Individual Case Reports and Associated Meningiomamentioning
confidence: 99%
“…As expected, all nine included studies were case reports from a hospital setting. One study reported on two individual patients, 19 while another reported on three individual patients. 20 Risk of bias within studies Risk of bias assessment was performed for each individual case report identified (n = 12).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since numerous publications have reported cases of meningiomas in patients treated with CPA since 2007 [15,[19][20][21][22][23], our practitioners therefore systematically questioned patients about their current or past use of one or more hormonal treatments.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cyproterone acetate (not currently FDA approved in United States for use in patients with prostate cancer) is known to cross blood-brain barrier (Denmeade and Isaacs 2002). Cyproterone acetate is also known to worsen prolactinoma and hence has the potential to result in PA among patients with occult or known pituitary adenoma (Raj et al 2018). In our review, 3 patients with prior/concurrent use of cyproterone acetate developed PA.…”
Section: Author's Recommendationsmentioning
confidence: 95%